Blue phosphorene/Sc2CX2 (X = O, F) van der Waals heterostructures as suitable candidates for water-splitting photocatalysts and solar cells. Issue 10 (2nd September 2020) - Li, Xiao-Hua; Wang, Bao-Ji; Wang, Guo-Dong; Ke, San-Huang
Abstract : Using DFT calculations, BlueP/Sc2 CX2 (X = O, F) heterostructures are found to have great potential in the field of solar energy applications. Abstract : Constructing two-dimensional (2D) van der Waals heterostructures with novel physical properties is regarded as a promising strategy to obtain desirable optoelectronic devices. Here, by systematic first-principles calculations, we demonstrate that the 2D blue phosphorene/Sc2 CX2 (X = O, F) van der Waals heterostructures are robust type-II band alignment semiconductors with an indirect band gap, and exhibit low exciton binding energies as well as having a strong light-harvesting ability in the UV-visible region. Remarkably, both are found to be potential photocatalysts for water splitting in acidic and/or neutral solutions. Interestingly, the external strain can significantly increase the power conversion efficiency (PCE) of the blue phosphorene/Sc2 CF2 heterostructure up to 20.87% (increased by 36%). These results indicate that the blue phosphorene/Sc2 CX2 heterostructures will have extensive application prospects in the field of solar energy utilization.